Safe Return - Martie Gillen; Meredeth A. Rowe (EDIS, 2012)
In the United States, more than 10,000 times each year a person with dementia becomes lost in the community and cannot find the way home. The quality of care people receive does not influence the likelihood of people with dementia to become lost. Even people who live in the best caregiving situations can become lost in the community. It can happen to anyone, even if the person does not have a tendency to wander. This revised 4-page fact sheet looks at why people with dementia become lost, how to prevent this from happening, and identify the best search strategies for finding someone who is lost. Written by Martie Gillen and Meredeth A. Rowe, and published by the UF Department of Family, Youth and Community Sciences, November 2012.